Indian migrant workers in GCC countries. Issue 2 (2nd July 2016) - Azhar, Muhammad
Abstract : India and the Gulf Cooperation Council (GCC) countries have age old relations. Indians and people from these countries have frequently travelled to each other's countries for trade as well as other activities. Indians have been traced in GCC countries for a long time. Indians going to those countries for business, work and other purposes have been a very old phenomenon. Even in pre-oil era, thousands of Indians went to earn a livelihood in GCC countries and many of them settled there forever. However, Indians going to work on a massive scale to these countries is a post-1973 oil era phenomena. The massive inflow of oil revenues consequent to the high rise in global oil price saw unprecedented level of economic development in these countries. However, such development required massive level of manpower, which these countries did not have and this is why these countries are characterized as capital rich labour scarce countries. The economic development in post-1973 oil era in these countries resulted in large scale import of manpower from abroad. As Indians were not new to these lands, the Indian workers also started migrating to these countries in search of employment and better life. Today Indians are present in each sector of economies of GCC countries. Millions of Indian migrant workers abound the GCC countries and contribute their bit in building those economies. However, this benefits them also as well as the Indian economy. These Indian migrant workers are crucial for both Indian as well as GCC countries. This study is a detailed probe into this phenomenon.